Market structure and competition policy : game theoretic approaches - Norman, George, 1946-; Thisse, Jacques François; Phlips, Louis (Cambridge University Press, 2000)
A wide-ranging contribution to the literature on industrial economics by leading scholars from Europe and North America, combining theory and applied case studies, on the sometimes surprising effects of competition or anti-trust policy on industry structure.